A large-scale pico-droplet array for viable bacteria digital counting and dynamic tracking based on a thermosetting oil. Issue 14 (28th June 2022) - Suo, Yuanjie; Yin, Weihong; Wu, Wenshuai; Cao, Wenjian; Zhu, Qiangyuan; Mu, Ying
Abstract : A simple and rapid method was developed for real-time monitoring and digital counting of bacterial growth, and it can provide dynamic information at high resolution in the process. Abstract : The rapid and accurate detection of viable bacteria is of great importance in food quality monitoring and clinical diagnosis. Escherichia coli ( E. coli ) is a major pathogenic bacterium, which causes potential threats to food safety and human health. Therefore, rapid and portable methods for preventing E. coli outbreaks are needed. Single cell analysis can be performed at the single-cell level, which has great advantages for analysis and diagnosis. Herein, we employed a thermosetting oil to generate a large-scale pico-droplet array for viable bacteria digital counting and dynamic tracking. In this array, the droplets can be solidified without any inducers due to the cross-linking reaction of the hydrosilation of vinyl silicone oil and hydrosilicone oil. Single E. coli cells were encapsulated in solidified droplets to form a microcolony. Resazurin was used as a fluorescent indicator to achieve amplification of bacterial growth signals. This method can achieve digital counting of viable E. coli cells in 4 h. We achieved real-time monitoring of E. coli cell growth and division in droplets. It is rapid, simple, and does not require a pre-enrichment process when compared to the traditional plate counting method. We successfully applied the method for the enumeration of E. coli in milk. In conclusion, the thermosetting oil enables the immobilization of droplets to achieve real-time monitoring and digital counting of bacterial growth without impairing the flexibility of droplet microfluidics, and it has the potential to provide dynamic information at high resolution in this process.